Consensus Statement on the Use of Botulinum Neurotoxin in the Middle East - Ali S; AL Bukhari F; Al Nuaimi K; Elenany H; Fakih-Gomez N; Ghannam S; Haidar R; Isse N; Labib N; Mosahebi A; Ravichandran S; Turkmani MG; et al. (Dove Medical Press, 2023)
Shazia Ali,1,2 Faten AL Bukhari,3 Khaled Al Nuaimi,4 Hossam Elenany,5 Nabil Fakih-Gomez,6 Sahar Ghannam,7 Rami Haidar,8 Nicanor Isse,9 Nancy Labib,9 Afshin Mosahebi,10 Simon Ravichandran,11 Mohammed G Turkmani,12 Christeen Youssef13 1Department of Dermatology, University of Wales College of Medicine, Cardiff, Wales, UK; 2TrueMe Medical Centre, Jeddah, Kingdom of Saudi Arabi; 3Department of Dermatology, Princess Nourah bint Abdulrahman University, Riyadh, Saudi Arabia; 4Department of Dermatology, College of Medicine, Sharjah University, Sharjah, United Arab Emirates; 5Department of Dermatology and Aesthetic Medicine, DaO Derma, Cairo, Egypt; 6Department of Facial Plastic Surgery, Fakih Hospital, Khaizaran, Lebanon; 7Department of Dermatology, Alexandria University, Alexandria, Egypt; 8Skin Experts Polyclinic, Dubai, United Arab Emirates; 9Department of Dermatology, Medcare Hospital and Clinics, Dubai, United Arab Emirates; 10Department of Plastic Surgery, Royal Free Hospital, London, UK; 11Clinetix Rejuvenation Ltd, Glasgow, Scotland; 12Derma Clinic, Riyadh, Kingdom of Saudi Arabi; 13Everlast Wellness Medical Center, Abu Dhabi, United Arab EmiratesCorrespondence: Simon Ravichandran, Clinetix Rejuvenation Ltd, Glasgow, Scotland, Email simonravi@clinetix.co.ukBackground: Aesthetic minimally invasive procedures have become very popular and culturally acceptable among Middle Eastern populations. Botulinum neurotoxin type A (BoNTA) is a valuable treatment modality for many cosmetic as well as therapeutic indications. The presence of BoNTA in our toolkit has revolutionized the field of aesthetic medicine to the point where it is now one of the most commonly performed cosmetic procedures worldwide. This consensus considers popular on- and off-label BoNTA indications in the Middle East.Methods: A multinational group of ten key opinion leaders, experts in facial plastic surgery and dermatology, convened the Middle East Aesthetics Consensus Group and reviewed the aesthetic applications of BoNTA. Recommendations and position statements were drafted based on the integration of the panel's clinical experience with published data, targeted to the practices implemented in the Middle Eastern and the global population.Results: Guidance statements are presented covering Middle Eastern facial characteristics and beauty ideals, BoNTA characteristics, pre-operative counselling, treatment indications and anatomical considerations, off-label and special uses including high-dose recommendations, and post-treatment advice. Throughout, an evidence-based approach to selection of products and injection techniques is provided, supplemented by the experts' advice on injections dosages and placement.Conclusion: This consensus reflects the knowledge and expertise of physicians practicing in the Middle East. The panel acknowledged the use of on-label indications and variability in the toxin formulations and immunogenicity and agreed upon a wide use of "off-label" indications.Keywords: aesthetic use, botulinum neurotoxin type A, consensus, Middle East